Experimental Study on Simulation Filling of New Underwater Cementitious Filling Material (NWC-FM) - Yanmei Ruan; Xu Luo; Shan Lin; Xingkai Pei (Advances in Civil Engineering)
To solve the problem of waste slag treatment of slurry shields, a reuse scheme in which waste shield mud is used to replace traditional karst cave grouting filling material which is proposed; thus, a new type of underwater cementitious filling material (NWC-FM) is developed. NWC-FM is convenient, inexpensive, and environmentally friendly. Its mix proportion is designed, and its mechanical performance is tested. According to the characteristics of karst caves, a semiclosed and pressurized karst cave simulation box is designed and manufactured to simulate grouting filling processes at construction sites, and an NWC-FM grouting simulation test is carried out. The results show that the fluidity of the NWC-FM slurry is good, and the strengths of the samples in the three groups of designed mix proportions meet the requirements of field construction. The underwater poured NWC-FM shows good fluidity, cohesion, nondispersibility, self-leveling, and self-compacting. After each pouring of NWC-FM material, a 2∼3 cm isolation layer eventually forms on the surface due to the action of the additives, which can effectively block the contact between water and NWC-FM and ensure the flatness of the underwater poured surface of the NWC-FM material. The average compressive strength of the NWC-FM consolidated core samples at 7 d, 14 d, and 28 d are 0.56 MPa, 0.72 MPa, and 0.79 MPa, respectively, meeting the technical strength requirements of construction sites. NWC-FM has strong underwater nondispersibility and moderate strength, which can well meet the requirements of karst cave filling treatment during shield construction of urban subways. Additionally, as a low-cost and environmentally friendly material, NWC-FM will greatly reduce the project cost and minimize environmental pollution.